Discovery of a novel eIF4E1.S allele conferring PVY resistance in Chinese tobacco (Nicotiana tabacum) landraces. (22nd June 2021) - Lin, Shifeng; Dewey, Ralph E.; Wang, Rengang; Ren, Xueliang; Wang, Zili; Zhang, Jishun; Long, Mingjin
Abstract: The tobacco eIF4E1 . S gene is a well‐recognized susceptibility factor for potato virus Y (PVY) and a dominant target locus for current PVY resistance breeding in tobacco. In this study, over 900 tobacco landraces from China were screened for resistance to PVY and the DNA sequence of eIF4E1 . S was analysed for all resistant accessions. Eight PVY‐resistant lines were identified from this screen, and a naturally occurring mutant allele of eIF4E1 . S carrying a single nucleotide insertion was discovered in seven, including a landrace called Kaiyangxiaoheiyan (Kaixiao), and designated eIF4E1.Kai . Knowledge of the mutant gene sequence enabled the development of a codominant PCR‐based marker that can distinguish eIF4E1.S/eIF4E1.Kai heterozygotes from both homozygous classes. Using this marker, we genotyped F2 plants segregating for the eIF4E1 . Kai mutant and confirmed the relationship between genotype and phenotype. The results described here provide valuable genetic insights into Chinese tobacco landraces as a source of naturally occurring PVY resistance, as well as a powerful tool for the molecular marker‐assisted breeding of tobacco varieties containing the resistance source eIF4E1.Kai .